The Norton anthology of poetry - Ferguson, Margaret W., 1948-; Salter, Mary Jo; Stallworthy, Jon (New York : W.W. Norton, 2005)
Long the classic anthology of poetry in English, The Norton Anthology of Poetry, Fifth Edition, adds to its wealth of known and loved poems a rich gathering of new poetry. Beginning with Beowulf, newly represented by selections from Seamus Heaney's dazzling translation, and continuing to the present day, The Norton Anthology of Poetry includes over 1,700 poems by 340 poets in the Regular Edition, and 1,100 poems by 250 poets in the Shorter. Many major figures--from Chaucer and Shakespeare to Ashbery and Walcott--have expanded sections, and a range of outstanding younger voices have been newly added. Concise annotations, biographical sketches, an Essay on Versification by Jon Stallworthy, and, new to this edition, an Essay on Poetic Syntax by Margaret Ferguson help readers understand and enjoy the poems
Includes bibliographical references and index
Keywords: English poetry; American poetry